Toward Personalized Cell Therapies: Autologous Menstrual Blood Cells for Stroke. (20th November 2011) - Rodrigues, Maria Carolina O.; Glover, Loren E.; Weinbren, Nathan; Rizzi, Jessica A.; Ishikawa, Hiroto; Shinozuka, Kazutaka; Tajiri, Naoki; Kaneko, Yuji; Sanberg, Paul R.; Allickson, Julie G.; Kuzmin-Nichols, Nicole; Garbuzova-Davis, Svitlana; et al.
Abstract : Cell therapy has been established as an important field of research with considerable progress in the last years. At the same time, the progressive aging of the population has highlighted the importance of discovering therapeutic alternatives for diseases of high incidence and disability, such as stroke. Menstrual blood is a recently discovered source of stem cells with potential relevance for the treatment of stroke. Migration to the infarct site, modulation of the inflammatory reaction, secretion of neurotrophic factors, and possible differentiation warrant these cells as therapeutic tools. We here propose the use of autologous menstrual blood cells in the restorative treatment of the subacute phase of stroke. We highlight the availability, proliferative capacity, pluripotency, and angiogenic features of these cells and explore their mechanistic pathways of repair. Practical aspects of clinical application of menstrual blood cells for stroke will be discussed, from cell harvesting and cryopreservation to administration to the patient.